Analisis Nilai-nilai dalam Tradisi Beguru di Kecamatan Timang Gajah Kabupaten Bener Meriah - Dea Riski; Emilda; Radhiah (Journal of Practice Learning and Educational Development, 2026)
This study aims to describe the values contained in the beguru tradition in Timang Gajah District, Bener Meriah Regency. This study employed qualitative research with descriptive analysis methods. The data source for this study was the beguru tradition in Gayo wedding customs in Timang Gajah District. The data consisted of advice conveyed in the beguru tradition in Timang Gajah District. The data collection techniques used in this study were recording, observing, and taking notes. This study employed a flow analysis technique. Based on the research results and discussion, it can be concluded that the advice in the beguru tradition contains values based on Notonegoro's theory. These values are classified into three categories: material values, vital values, and spiritual values, which include beauty, goodness, religiousness, and truth.